The textual transmission of the New Testament: manuscripts, variants, and authority - Chapa, Juan (Text-critical studies, 2025)
"...Juan Chapa offers nuanced discussions of many topics that currently occupy the field of textual criticism, including debates over the dating of New Testament papyri, the preference for the codex, the liturgical use of texts, the presence of nomina sacra, textual variants, the establishment of the New Testament text, problems with the term original, and the challenge of textual fluidity. His unique approach illustrates how a Catholic perspective, the rule of faith, and the Latin textual tradition can inform our understanding of the origin, preservation, and authority of the New Testament text. Chapa's work contributes a distinctively Catholic voice to the largely Protestant chorus that has dominated the field, thus filling a lacuna in contemporary text-critical conversations." -- Publisher, page four of cover